Application of Passenger and Vehicle Departure Services to the Ticketing System Environment at Ketapang Ferry Port, Banyuwangi Regency, East Java Province - Yohan Wibisono; Budi Mantoro; Carolina Farah Diba (IWJ : Inland Waterways Journal, 2021)
The Ketapang ferry port is a commercial ferry port that has implemented "Ticketing Digitalization" which means that service users can easily buy tickets by online. The large number of service users/customers in this ferries urges service providers to provide convenience and effectiveness for service users with online-based media so that customers can access information about crossings to ticket reservations well before the scheduled departure to be determined. Based on the Regulation of the Minister of Transportation of the Republic of Indonesia Number 19 of 2020 concerning the Operation of Electronic Crossing Transportation Tickets, e-tickets for ferry transportation can be ordered through: a) information technology-based applications or websites; b) ticket sales place that provides an electronic system; or c) a standalone ticket vending machine. In the application of the online-based ticketing system, it was found that there were still problems, namely related to the selection of the schedule on the online ticket system where in the selection of the departure schedule the service user could only determine the port entry hours. The time for entering the port uses an hourly time interval and cannot know or even determine which ship to use. There is also no information on the remaining load capacity at the selected port of entry.